Pengaruh Manajemen Kas terhadap Profitabilitas dan Likuiditas Perusahaan Manufaktur yang Terdaftar di BEI tahun 2022-2024 - Mar’ah Aulia; Nawrah Qanita Irfan; St Ainun Khairunnisa; Silviah Bahrun; Falisha Sulistiawati; Nasrullah Asri (Jurnal Pengabdian Masyarakat, 2026)
This study examines the influence of cash management on profitability and liquidity in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2022 - 2024. Cash management plays a crucial role in ensuring operational continuity and financial stability, making it essential in determining company performance. This research aims to analyze how cash management affects profitability, measured by Return on Assets (ROA) and Return on Equity (ROE), as well as liquidity, measured by Current Ratio (CR) and Quick Ratio (QR). The research uses a quantitative descriptive method with secondary data obtained from audited financial statements. A multivariate analysis model is employed to test the relationship between variables. The findings indicate that cash management has a significant effect on both profitability and liquidity, suggesting that effective cash handling enhances financial performance and strengthens short-term financial capacity. These results highlight the importance of optimizing cash utilization to maintain operational efficiency and support long-term financial sustainability.